2006
DOI: 10.1097/01.aog.0000245786.86267.80
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Papillomavirus Vaccines on Vulvar, Vaginal, and Anal Intraepithelial Lesions and Vulvar Cancer

Abstract: II-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
91
0
16

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(110 citation statements)
references
References 47 publications
3
91
0
16
Order By: Relevance
“…All of these tissues with abnormal cytology were random investigated in various histopathology types such as chronic inflammation, Leiomyoma etc, including intraepithelial neoplasia and some of vulva tissues with keratinizing histological type such as lichen sclerosus was likely to be non-HPV-related and usually found in older women. (ICO WHO Information center, 2014;Smith et al, 2007;Madeleine et al, 1997) Furthermore, not all of vulva and Vaginal cancers are induced by HPV, it dependent on the several factors such as age, cancer history, type of cancer diagnosed, etc (Hampl et al, 2006). However, our results of HPV DNA showed that 1/1 sample of vulva intraepithelial neoplasia (VIN) and 3/3 samples of Vaginal intraepithelial neoplasia (VAIN) in this study found HPV infection.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…All of these tissues with abnormal cytology were random investigated in various histopathology types such as chronic inflammation, Leiomyoma etc, including intraepithelial neoplasia and some of vulva tissues with keratinizing histological type such as lichen sclerosus was likely to be non-HPV-related and usually found in older women. (ICO WHO Information center, 2014;Smith et al, 2007;Madeleine et al, 1997) Furthermore, not all of vulva and Vaginal cancers are induced by HPV, it dependent on the several factors such as age, cancer history, type of cancer diagnosed, etc (Hampl et al, 2006). However, our results of HPV DNA showed that 1/1 sample of vulva intraepithelial neoplasia (VIN) and 3/3 samples of Vaginal intraepithelial neoplasia (VAIN) in this study found HPV infection.…”
Section: Discussionmentioning
confidence: 56%
“…And we observed that HPV 18 could be detected as co-infection with other high risk types and all of low risk type was never found as single infection in this study. Although the most three common HPV typedistribution in vulva and Vaginal in our study showed slightly different from the other reports (Ramet et al, 2010;ICO WHO Information center, 2014;Hampl et al, 2007;Baldez da Silva et al, 2012), due to the different HPV detection methods, amount or type of sample collection, population characteristic, etc, but there are several studied reported which found that high risk HPV type such as HPV 16,18,31,33,35,45,51,52,56 or 58 have been associated with vulva, vagina, penis, anus or cervical cancers and abnormal lesions (Giuliano et al, 2008;Baldez da Silva et al, 2012;Hampl et al, 2007;De Vuyst et al, 2009 Otherwise, the variety of population group, sample selection and histological diagnosis results were to be the important factors which were used to be considerable (Hampl et al, 2006;Giuliano et al, 2008) This finding demonstrated that HPV 16 was the most common HPV type present in vulva and Vaginal tissues with abnormal cytology lesions and cancer cells while HPV 18 and the other types showed less frequently for both organs from Thai women and the HPV type distribution of vulva and Vaginal were not variety as cervical cells. However, it is interesting baseline data on HPV prevalence of vulva and Vaginal abnormal/cancer from Thai women, which there are limited evidences available and both of these cancers are more less frequency compared to cervical cancer, although the sample size in this study was small and did not represented overall incidence and prevalence of Thai women population.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports in recent years, there have been significant rising trend of VC in younger age. 5 In this study, the age distribution ranges from 24 to 88-yearold, with average age 57.09 ± 12.93 years old, and with a peak age of 56 to 61-year-old. The mean age of onset at different period from 2002-2012 was 63.38 ± 10.38 years which dropped in 2010-2012 to 54.33 ± 14.86 years.…”
Section: Discussionmentioning
confidence: 76%
“…Although the incidence of vaginal and vulvar cancers is low compared to other gynecologic cancers, the surgical treatment of these cancers is often mutilating and traumatic for women. 23,24 Additionally, the prognosis for vaginal cancer patients is very poor. 23 A large population-based study estimated that wide implementation of HPV vaccination would prevent approximately one half of vulvar carcinomas in women younger than aged 56 and approximately two-thirds of the intraepithelial precursor lesions in the lower genital tract.…”
Section: Current Gynecologic Cancer Mortality Rates and Potential Futmentioning
confidence: 99%
“…23 A large population-based study estimated that wide implementation of HPV vaccination would prevent approximately one half of vulvar carcinomas in women younger than aged 56 and approximately two-thirds of the intraepithelial precursor lesions in the lower genital tract. 24 There are several related areas in which NCCCP grantees can readily engage in to assist with this. It is suggested that educating healthcare workers about the importance of provider recommendations for parents may be the single most important way to increase HPV vaccination among children.…”
Section: Current Gynecologic Cancer Mortality Rates and Potential Futmentioning
confidence: 99%